University in the Period of Changing the Information Flow Model - Lewandowska, Maria; Stachowiak, Beata (Wydawnictwo Naukowe WNPiD UAM, 2019)
The article aims to present the results of the study regarding the view of modern students at the university. Several research problems were formulated as follows: what sources of information and knowledge about the world do contemporary students use; what are the main goals of higher education according to modern students; why are modern students deciding to start a higher education course; who is an academic teacher for a modern student? The research tool was a questionnaire made available to the students electronically. Research has shown that the University is one of the sources of information for 65% of students participating in the study. Only the Internet has obtained more indications. Futhermore, Respondents regarded the key objectives of higher education as contributing to the intellectual development of students, vocational training and awarding academic degrees and issuing diplomas. The main reasons why the respondents chose to study at a higher school were: the desire to obtain higher education, the desire for intellectual development and the acquisition of specific practical skills. Academic teachers are for students who have answered the open question, above all persons transferring knowledge. 21% of them gave the answer “master” and all synonyms of this term.

Artykuł ma na celu zaprezentowanie wyników badań dotyczących poglądów współczesnych studentów na uniwersytet. Sformułowano kilka problemów badawczych: z jakich źródeł informacji i wiedzy o świecie korzystają współcześni studenci; jakie są główne cele szkolnictwa wyższego według współczesnych studentów; dlaczego współcześni studenci decydują się na rozpoczęcie studiów wyższych; kim jest nauczyciel akademicki dla współczesnego studenta? Narzędziem badawczym był kwestionariusz ankiety udostępniony studentom drogą elektroniczną. Badania wykazały, że uniwersytet jest jednym ze źródeł informacji dla 65% studentów biorących udział w badaniu. Więcej wskazań uzyskał jedynie Internet. Ponadto, respondenci za kluczowe cele szkolnictwa wyższego uznali przyczynianie się do rozwoju intelektualnego studentów, przygotowanie zawodowe oraz przyznawanie stopni naukowych i wydawanie dyplomów. Głównymi powodami, dla których respondenci zdecydowali się podjąć studia w szkole wyższej były: chęć zdobycia wyższego wykształcenia, chęć rozwoju intelektualnego i chęć nabycia określonych umiejętności praktycznych. Nauczyciele akademiccy są dla studentów, przede wszystkim, osobami przekazującymi wiedzę. 21% spośród ankietowanych udzieliło odpowiedzi „mistrz” (lub użyło synonimu tego słowa).
Uniwersytet w okresie zmiany modelu przepływu informacji
Keywords: University; sources of information; academic teacher; higher education; uniwersytet; źródła informacji; nauczyciel akademicki; szkolnictwo wyższe